Endoscopic Transnasal Odontoidectomy With Anterior C1 Arch Preservation and Anterior Vertebral Column Reconstruction in Patients With Irreducible Bulbomedullary Compression by Complex Craniovertebral Junction Abnormalities: Operative Nuance. Issue 3 (September 2016) - Iacoangeli, Maurizio; Di Rienzo, Alessandro; Colasanti, Roberto; Re, Massimo; Nasi, Davide; Nocchi, Niccolò; Alvaro, Lorenzo; di Somma, Lucia; Dobran, Mauro; Specchia, Nicola; Scerrati, Massimo
Abstract : BACKGROUND: During the past decades, the transoral transpharyngeal approach has been advocated as the standard route for the removal of odontoid causing an irreducible symptomatic neural compression. However, it may be potentially associated with a significant built-in morbidity because of the splitting of the soft palate for an adequate working angle, tracheostomy, and incision of the oral mucosa, causing exposure to a higher risk of infection by oral flora. OBJECTIVE: To describe our experience with the minimally invasive pure endoscopic transnasal odontoidectomy in patients with bulbomedullary compression affected by complex anterior craniovertebral junction abnormalities. METHODS: Five patients underwent a pure endoscopic neuronavigation-assisted transnasal odontoidectomy with anterior C1 arch preservation. Moreover, the anterior cervical spine column was reconstructed by filling the gap between the C1 arch and the residual C2 body with autologous/artificial bone. Neither tracheostomy nor enteral tube feeding were needed in any case. RESULTS: A postoperative neurological improvement was observed in all patients. Postoperative imaging confirmed a satisfactory spinal cord decompression with cervical anterior column arthrodesis, and without evidence of instability at follow-up, so far. CONCLUSION: The endoscopic transnasal approach seems to represent an efficient and safe alternative to the transoral route for the resection of odontoid process causing irreducible bulbomedullary compression. It provides a straightforward and minimally invasive natural surgical corridor to the anterior craniocervical junction, allowing a better working angle with preservation of spine biomechanics, while minimizing potential comorbidities.